Quality of service over heterogeneous network with MPLS back bone - Mahmoud, Omer; Anwar, Farhat; Ali, Sellami; Hassan Abdalla Hashim, Aisha (2012)
Internet growth in recent years has encouraged many new applications to be provided for the end user. However, providing and maintaining high quality of service for these new applications is a challenging matter that is getting the attention of many many researchers nowadays. The QoS challenge is emanating from the diversity of these applications, in term of bandwidth requirements and high sensitivity to delay and delay variation. Three main architectures were proposed by IETF in an effort to make the IP QoS a reality. They are integrated services (Intserv), differentiated services (DiffServ) and multiprotocol label switching (MPLS). Sometimes perceived as competitor, these architectures are in fact complementary developments that approach the QoS challenge from different network perspectives. Thus these approaches can work together in a manner that provides a global QoS within Heterogeneous network. This paper aims to propose and discusses an improved admission control mechanism in order to achieve a global QoS in the HN Network. The proposed mechanism uses MPLS-TE tunnels at the core of Heterogeneous networks to maintain QoS for inter-domain flows and applications.